2020
DOI: 10.3390/pharmacy8040229
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Objective Structured Clinical Examination Training Approach for Training Pharmacy Students in Diabetes Mellitus Counseling: A Randomized Controlled Trial

Abstract: Pharmacists’ tasks are multifaceted and include, for example, vital counseling and communication skills. Objective Structured Clinical Examinations (OSCEs) could be used to train pharmacy students in these skills. Our study sought to determine the efficacy of our OSCE training approach for training pharmacy students’ counseling and communication skills on diabetes mellitus compared to a control group. This randomized controlled study was conducted with pharmacy students using a pre-post-design. The interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This study found significant increases in self-confidence through the application of OSCEs, in agreement with findings in the literature. 22 , 33 - 35 Moreover, the majority of students in this study agreed that OSCEs should be implemented in future clinical pharmacy courses for training their counseling skills. These findings support students’ acceptance of OSCEs, which is in line with findings of other studies.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This study found significant increases in self-confidence through the application of OSCEs, in agreement with findings in the literature. 22 , 33 - 35 Moreover, the majority of students in this study agreed that OSCEs should be implemented in future clinical pharmacy courses for training their counseling skills. These findings support students’ acceptance of OSCEs, which is in line with findings of other studies.…”
Section: Discussionmentioning
confidence: 78%
“…These findings support students’ acceptance of OSCEs, which is in line with findings of other studies. 22,33,36 Although the control group’s training with the SmPCs was rather disliked by the students, the positive results, including the significant increase in the analytical checklist score, global rating scale score, and self-assessment questionnaire score from pre- to post-training OSCEs, indicate a beneficial contribution on students’ counseling skills. Nevertheless, regarding the analytical checklist and self-assessment questionnaire, the OSCE-trained group was superior.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown that formative assessment with immediate feedback during the learning phase improves clinical competence [ 21 ]. OSCE training was found to be effective in improving counselling and communication skills and self-confidence [ 12 ]. Students found OSCE to be enjoyable and a welcome change from routine [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, standardized patients at OSCE stations have been used to assess resident doctors' ability to counsel vaccine-hesitant patients 23 , and medical students' ability to counsel patients with obesity 24 . OSCE has been used to improve communication, interpersonal and counseling skills 25 . Future training models for hormonal IUD scale up may want to explore use of OSCE as a training tool rather than (or in addition to) as an assessment tool.…”
Section: Discussionmentioning
confidence: 99%